Distribution and biotransformation of therapeutic antisense oligonucleotides and conjugates. Issue 10 (October 2021) - Weidolf, Lars; Björkbom, Anders; Dahlén, Anders; Elebring, Marie; Gennemark, Peter; Hölttä, Mikko; Janzén, David; Li, XueQing; Andersson, Shalini
Graphical abstract: Highlights: Targeting ASOs to other organs than the liver is currently challenging. Early generation of disposition data supports regulatory interactions. No one bioanalytical method addresses all questions for an oligonucleotide program. 34 S labelled internal standards apply to any PS backbone containing oligonucleotide. Need for ASO biotransformation data will increase with diverse patient populations. Abstract: Drug properties of antisense oligonucleotides (ASOs) differ significantly from those of traditional small-molecule therapeutics. In this review, we focus on ASO disposition, mainly as characterized by distribution and biotransformation, of nonconjugated and conjugated ASOs. We introduce ASO chemistry to allow the following in-depth discussion on bioanalytical methods and determination of distribution and elimination kinetics at low concentrations over extended periods of time. The resulting quantitative data on the parent oligonucleotide, and the identification and quantification of formed metabolites define the disposition. Proper quantitative understanding of disposition is pivotal for nonclinical to clinical predictions, supports communication with health agencies, and increases the probability of delivering optimal ASO therapy to patients.